Pathophysiology of Disease An Introduction to Clinical Medicine - Hammer, Gary D.; McPhee, Stephen J. (McGraw-Hill Education, 2019)
The goal of this trusted text is to introduce you to clinical medicine by reviewing the pathophysiologic basis of 132 diseases (and associated signs and symptoms) commonly encountered in medical practice. The authors, all experts in their respective fields, have provided a concise review of relevant normal structure and function of each body system, followed by a description of the pathophysiologic mechanisms that underlie several common diseases related to that system. The accessible presentation features high-quality full-color illustrations, and numerous tables and diagrams. Each chapter of Pathophysiology of Disease concludes with a collection of case studies and questions designed to test your understanding of the pathophysiology of each clinical entity discussed. These case studies allow you to apply your knowledge to specific clinical situations. Detailed answers to each case study question are provided at the end of the book. This unique interweaving of physiological and pathological concepts will put you on the path toward thinking about signs and symptoms in terms of their pathophysiologic basis, giving you an understanding of the "why" behind illness and treatment.